Evaluation of the New ISGLS Definitions of Typical Posthepatectomy Complications. (June 2019) - Birgin, E.; Tesfazgi, W.; Knoth, M.; Wilhelm, T.J.; Post, S.; Rückert, F.
Background and Objectives: The International Study Group of Liver Surgery established the first internationally standardized definitions and grading for posthepatectomy hemorrhage, posthepatectomy liver failure, and bile leakage. We aimed to correlate these definitions and grades of complications with objective parameters of the postoperative course, namely, mortality and length of stay, to assess the usefulness in clinical routine. Methods: A total of 415 patients underwent hepatic surgery between 2004 and 2014. Uni- and multivariate analyses were made for correlations of posthepatectomy hemorrhage, posthepatectomy liver failure, and bile leakage with perioperative parameters and mortality. Results: Of the total, 25 (6.1%) patients developed a posthepatectomy hemorrhage Grade A, 3 (0.7%) patients a posthepatectomy hemorrhage Grade B, and 1 (0.2%) patient a posthepatectomy hemorrhage Grade C; 23 (5.5%) patients had a posthepatectomy liver failure Grade A, 24 (5.8%) patients a posthepatectomy liver failure Grade B, and 7 patients (1.6%) a posthepatectomy liver failure Grade C. Bile leakage Grade A occurred in 10 (2.4%) patients, bile leakage Grade B in 24 (5.8%) patients, and bile leakage Grade C in 7 (1.6%) patients. Mortality was significantly increased in patients with posthepatectomy hemorrhage Grades B and C and in patients with posthepatectomy liver failure Grades A, B, and C. Three (42.9%) patients with bile leakage Grade C died. Conclusion: Our data indicate that the new definitions correlate well with mortality and duration of hospital stay.